Non-invasive pneumococcal pneumonia due to vaccine serotypes: A systematic review and meta-analysis. (February 2022) - Lansbury, Louise; Lim, Benjamin; McKeever, Tricia M; Lawrence, Hannah; Lim, Wei Shen
Summary: Background: Non-invasive pneumococcal pneumonia causes significant morbidity and mortality in older adults. Understanding pneumococcal sero-epidemiology in adults ≥50 years is necessary to inform vaccination policies and the updating of pneumococcal vaccines. Methods: We conducted a systematic review and random-effects meta-analysis to determine the proportion of community-acquired pneumonia (CAP) in people ≥50 years due to pneumococcus and the proportion caused by pneumococcal vaccine serotypes. We searched MEDLINE, EMBASE and PubMed from 1 January 1990 to 30 March 2021. Heterogeneity was explored by subgroup analysis according to a) patient group (stratified versus age) and depth of testing, b) detection/serotyping method, and c) continent. The protocol is registered with PROSPERO (CRD42020192002). Findings: Twenty-eight studies were included (34, 216 patients). In the period 1–5 years after introduction of childhood PCV10/13 immunisation, 18% of CAP cases (95% CI 13–24%) were attributable to pneumococcus, with 49% (43–54%) of pneumococcal CAP due to PCV13 serotypes. The estimated proportion of pneumococcal CAP was highest in one study that used 24-valent serotype-specific urinary-antigen detection (ss-UAD)(30% [28–31%]), followed by studies based on diagnostic serology (28% [24–33%]), PCR (26% [15–37%]), ss-UAD14 (17% [13–22%]), and culture alone (14% [10–19%]). A higher estimate was observed in Europe (26% [21–30%] than North America (11% [9–12%]( p <0·001). PCV13-serotype estimates were also influenced by serotyping methods. Interpretation: Non-invasive pneumococcal CAP and vaccine-type pneumococcal CAP remains a burden in older adults despite widespread introduction of pneumococcal infant immunisation. Studies heavily reliant on ss-UADs restricted to vaccine-type serotypes may overestimate the proportion of potentially vaccine-preventable pneumococcal pneumonia. Sero-epidemiological data from low-income countries are lacking. Funding: The National Institute for Health Research (NIHR) Nottingham Biomedical Research Centre, UK, provided salary support for this study.